Endovascular Repair for a Ruptured AAA due to a Combined Type IIIb and Ia Endoleak - Konstantinos Ioannis Avgerinos; Nikolaos Melas; Athanasios Saratzis; Marianthi V. Tympanidou; Nikolaos Saratzis; Ioannis Lazaridis (Case Reports in Vascular Medicine)
We report a case of a ruptured abdominal aortic aneurysm (AAA) caused by a combined type IIIb and Ia endoleak. Also, we propose the mechanism that resulted in this combined endoleak. Specifically, a 71-year old-man, with a previous history of endovascular aneurysm repair (EVAR) for an AAA, was diagnosed with a contained rupture. CT scan depicted a type Ia endoleak and a migrated Talent endograft. A proximal aortic cuff sealed the endoleak, but intraoperative angiography revealed that a type IIIb endoleak coexisted due to fabric tear close to the Talent bifurcation. A second aortic cuff could not seal the fabric tear; so, in-lay parallel limbs were sequentially deployed as a “kissing endograft” technique inside the cuff. Simultaneous treatment of combined type IIIb and Ia endoleaks has not yet been described. Maybe the type IIIb endoleak is the primary entity causing sac enlargement, neck recontouring, proximal migration, and ultimately type Ia endoleak, which leads to huge enlargement and rupture. Placement of an aortic cuff to seal the proximal endoleak/migration and kissing endografts limbs for the fabric tear seems a safe option in such patients.